Folate-related polymorphisms in gastrointestinal stromal tumours: susceptibility and correlation with tumour characteristics and clinical outcome - Angelini, Sabrina; Ravegnini, Gloria; Nannini, Margherita; Lorenzo Bermejo, Justo; Musti, Muriel; Pantaleo, Maria A.; Fumagalli, Elena; Venturoli, Nicola; Palassini, Elena; Consolini, Nicola; Casali, Paolo G.; Biasco, Guido; et al. (European journal of human genetics, 2015)
The folate metabolism pathway has a crucial role in tumorigenesis as it supports numerous critical intracellular reactions, including DNA synthesis, repair, and methylation. Despite its importance, little is known about the influence of the folate pathway on gastrointestinal stromal tumour (GIST), a rare tumour with an incidence ranging between 6 and 19.6 cases per million worldwide. The importance of folate metabolism led us to investigate the influence of polymorphisms in the genes coding folate-metabolising enzymes on GIST susceptibility, tumour characteristics and clinical outcome. We investigated a panel of 13 polymorphisms in 8 genes in 60 cases and 153 controls. The TS 6-bp deletion allele (formerly rs34489327, delTInsTTAAAG) was associated with reduced risk of GIST (OR=0.20, 95% CI 0.05-0.67, P=0.0032). Selected polymorphisms in patients stratified by age, gender, and other main molecular and clinical characteristics showed that few genotypes may show a likely correlation. We also observed a significant association between the RFC AA/AG genotype and time to progression (HR=0.107, 95% CI 0.014-0.82; P=0.032). Furthermore, we observed a tendency towards an association between the SHMT1 variant allele (TT, rs1979277) and early death (HR=4.53, 95% CI 0.77-26.58, P=0.087). Aware of the strengths and limitations of the study, these results suggest that polymorphisms may modify the risk of GIST and clinical outcome, pointing to the necessity for further investigations with information on folate plasma levels and a larger study population.
Online 17 September 2014
Gesehen am 27.07.2020